A Scan and Study of Primary Health Care Models for Francophone Communities in Minority Settings Accross Canada - Canadian Association of Community Health Centres et Société Santé en français (2016)
pages: 40

Case studies: Primary health service delivery models for the Francophone minority - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
In several regions of the province, Francophones are in a minority situation. In several places, health services in French are minimal or even non-existent. Many stakeholders are trying to find solutions to improve or implement health services in French. Often these solutions are not always easy to identify or put in place. In this context, the Erie St. Clair/SouthWest French Language Health Planning Entity has used the services of a consultant who did an analysis of best practices in minority situations across North America and in other countries. This first analysis consists of a brief description of 352 practices developed to meet the needs of minority populations receiving few, if any, health services in their communities. Following this report, we have continued this research jointly with the Waterloo Wellington, Hamilton, Niagara, Haldimand Brant Entity2 and the French Health Network of Central Southwestern Ontario. Our purpose was to be able to identify 5 or 6 best practices in minority situations that might be applicable in our respective regions under the subject areas: primary health care, seniors care, mental illness and chronic disease. Each of the partners could study identified practices and ask more detailed explanations on certain practices that seemed more appropriate to respond to their local needs.
pages:

Études de cas sur les modèles de livraison de services de santé primaire pour les francophones en situation minoritaire - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
pages: 98

Ma santé, en français s'il vous plaît ! Une proposition qui traite des besoins des franco-ontariens et des franco-ontariennes de Thunder Bay en ce qui a trait aux soins de santé primaires - Larouche, Jérémie (Association des Francophones du Nord-Ouest de l'Ontario, L'Accueil francophone de Thunder Bay, Réseau francophone de santé du Nord de l'Ontario, 2007)